2016
DOI: 10.1180/claymin.2016.051.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite nanotubes: prospects and challenges of their use as additives and carriers – A focused review

Abstract: There is increasing research interest in potential applications of halloysite as fillers for polymer composites, controlled drug delivery, carriers for the supply and sustained release of active agents for anticorrosion coatings, in nanoreactors or nanotemplates, and for the uptake of contaminants or pollutants and support for catalysts. In this review, recent findings in terms of the prospects and challenges of using halloysite nanotubes (HNTs) in different polymeric matrices targeting a range of old and new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…Zn/TiO 2 oxides deposited on the halloysite surface represent anti-microbial properties [5], and can be used as photocatalysts for the removal of organic (and with additional surface treatment NO x ) pollutants [14]. The tubular morphology enables its use as a container for corrosion inhibitors [3,5]. The adsorption properties and biological activities of the so-called spheroidal halloysites differ significantly from those of the tubular ones, due to their significantly different morphology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zn/TiO 2 oxides deposited on the halloysite surface represent anti-microbial properties [5], and can be used as photocatalysts for the removal of organic (and with additional surface treatment NO x ) pollutants [14]. The tubular morphology enables its use as a container for corrosion inhibitors [3,5]. The adsorption properties and biological activities of the so-called spheroidal halloysites differ significantly from those of the tubular ones, due to their significantly different morphology.…”
Section: Introductionmentioning
confidence: 99%
“…With the preparation of halloysite nanocomposites/hybrids novel types of materials with desirable properties can be generated. Zn/TiO 2 oxides deposited on the halloysite surface represent anti-microbial properties [5], and can be used as photocatalysts for the removal of organic (and with additional surface treatment NO x ) pollutants [14]. The tubular morphology enables its use as a container for corrosion inhibitors [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HNTs, at 1–7 wt%, have also been successfully incorporated into polyethylene terephthalate as nanocontainers of antimicrobial agents for active packaging . PLA nanocomposites with 5 wt% HNTs showed an increase of 43% in the tensile strength of PLA due to the formation of hydrogen bonds between the hydroxyl groups of PLA chains and the outer‐surface siloxane groups of the HNTs . Bendahou et al used zeolites as nanofillers in a PLA matrix, obtaining important improvements in barrier and antimicrobial characteristics as well as improved mechanical behaviour (high modulus and high tensile strength).…”
Section: Introductionmentioning
confidence: 99%
“…15 PLA nanocomposites with 5 wt% HNTs showed an increase of 43% in the tensile strength of PLA due to the formation of hydrogen bonds between the hydroxyl groups of PLA chains and the outer-surface siloxane groups of the HNTs. 16 Bendahou et al 17 used zeolites as nanofillers in a PLA matrix, obtaining important improvements in barrier and antimicrobial characteristics as well as improved mechanical behaviour (high modulus and high tensile strength). PLA/nanoclay composites are interesting materials for active packaging with environmentally friendly performance, as reported by Lorite et al 18 Jampilek and Kráľová 4 suggested that bio-nanocomposites, using SiO 2 , offer good packaging properties due to their fine dispersion, increased mechanical strength, reduced gas permeability and improved water resistance.…”
Section: Introductionmentioning
confidence: 99%